First, rearrange the expression as:
(-3x^3y^4z^2)(xyz^2)(-x^5y^2z) =>
(-3x^3y^4z^2)(xyz^2)(-1x^5y^2z) =>
(-3 * -1)(x^3 * x * x^5)(y^4 * y * y^2)(z^2 * z^2 * z) =>
3(x^3 * x * x^5)(y^4 * y * y^2)(z^2 * z^2 * z)
Next, use this rule for exponents to rewrite the expression:
a = a^color(red)(1)
3(x^3 * x^color(red)(1) * x^5)(y^4 * y^color(red)(1) * y^2)(z^2 * z^2 * z^color(red)(1))
Now, use this rule of exponents to complete the evaluation:
x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))
3(x^color(blue)(3) * x^color(red)(1) * x^color(green)(5))(y^color(blue)(4) * y^color(red)(1) * y^color(green)(2))(z^color(blue)(2) * z^color(green)(2) * z^color(red)(1)) =>
3x^(color(blue)(3)+color(red)(1)+color(green)(5))y^(color(blue)(4)+color(red)(1)+color(green)(2))z^(color(blue)(2)+color(green)(2)+color(red)(1)) =>
3x^9y^7z^5